FORMATION OF THE PROFESSIONAL READINESS OF THE FUTURE TEACHERS OF IMITATIVE ART - Nosachenko, T.B. (Pedagogy of Higher and Secondary Education, 2007)
The article smooth the problem ofprofessional preparation of the future teachers of imitative art in the process study «Pedagogical drawing».